Dukungan Sosial sebagai Penyangga Stres Karier pada Dewasa Awal: Telaah Literatur Tematik tentang Quarter-Life Crisis - Nazhif Robbani, Achmad; Nafisatuzzahra, Nafisatuzzahra (FKIP Universitas Islam Jember, 2025)
Early adulthood is a developmental stage highly susceptible to career stress, especially as individuals face increasing pressure to achieve economic stability, professional success, and identity consolidation. This study aims to systematically explore the role of social support in helping emerging adults cope with career-related stress and the quarter-life crisis. Using a thematic literature review approach, various forms of social support, emotional, informational, instrumental, and companionship, were analyzed in relation to their impact on psychological well-being. The findings indicate that strong social support serves as a buffer against career stress, enhances self-confidence, and facilitates adaptation during life transitions. Support from family and peers significantly contributes to resilience, while involvement from educational institutions through mentorship programs and career counseling is recommended as a long-term preventive strategy. Further research using qualitative and longitudinal approaches is encouraged to explore individuals’ subjective experiences in deriving meaning from the social support they receive during this critical life phase. These findings are relevant for developing inclusive and responsive educational and mental health policies tailored to the needs of the younger generation.